Sistematik Literatur Review (SRL) Asam Lambung Naik - Usiono Usiono; Devita Aulia Putri (Pusat Riset dan Inovasi Nasional, 2024)
The stomach is a vital organ for the body which is quite susceptible to injury or damage. One of the factors that influences stomach performance is the food intake consumed daily. Negligent lifestyle habits, strict diests, environmental factors and srees can also causes of stomach acid, the technique used is the systematic literature review .SRL is a research method that aims to identify, study and interpret data in journals systematically with specified stages. The conclusion obtained from the research result is that there are 9 factors that cause gastritis or stomach acid, diet including type ogf food, frequency of eating and portion sizes, strees, coffee comsumption, alcohol comsumption, smoking habits gender and age. For treatment, proton pump inhibitor drugs such as omeprazole, lansoprazole, esomeprazole and pantoprazole to treat stomach acid. How to deal with stomach acid, eat soft foods that are easy to digest, such as porridge, vegetables, biscuoit and don’t eat foods that have strong or spycy flavours. And drink lots of warm water.